2021
DOI: 10.1159/000514573
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pathology and Occasionally Detectable Intraocular Severe Acute Respiratory Syndrome Coronavirus-2 RNA in Five Fatal Coronavirus Disease-19 Cases

Abstract: Introduction In December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic broke out. The virus rapidly spread globally, resulting in a major world public-health crisis. The major disease manifestation occurs in the respiratory tract. However further studies documented other systemic involvement. This study investigate histopathologic eye changes in post-mortem material of Coronavirus Disease 2019 (COVID-19) patients. Methods Sections of formalin-fixed, paraffin-embedded eyes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 15 publications
(23 reference statements)
2
46
0
Order By: Relevance
“…[20][21][22] Postmortem ocular tissue studies have demonstrated evidence of intraocular SARS-CoV-2 in some cases of COVID-19. 23,24 Documented severe visual loss related to COVID-19 has been reported, including acute retinal necrosis 25 and acute viral retinitis, 26 with confirmed SARS-CoV-2 positivity on vitreous testing. Greater attention to potentially pathogenic retinal damage and infection is warranted.…”
mentioning
confidence: 99%
“…[20][21][22] Postmortem ocular tissue studies have demonstrated evidence of intraocular SARS-CoV-2 in some cases of COVID-19. 23,24 Documented severe visual loss related to COVID-19 has been reported, including acute retinal necrosis 25 and acute viral retinitis, 26 with confirmed SARS-CoV-2 positivity on vitreous testing. Greater attention to potentially pathogenic retinal damage and infection is warranted.…”
mentioning
confidence: 99%
“…This choroidal inflammation may be generated solely by the entry of SARS-CoV-2 via the angiotensin-converting enzyme 2 receptor (ACE) in the endothelium. The presence and abundance of this receptor has already been found higher in COVID-19 fatal cases compared to controls [17]. In these patients the accumulation of mononuclear cells and neutrophils in the lumen and intima of choriocapillaris may prove the viral trigger for white dot syndromes.…”
Section: Discussionmentioning
confidence: 85%
“…These findings were not observed in control eyes, suggesting that they were related to COVID-19. [23] SARS-CoV-2 RNA was detected in three enucleated eyes of 14 dead COVID-19 patients. [24] The findings thus far suggest ocular involvement in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 93%